2015
DOI: 10.1093/nar/gkv776
|View full text |Cite
|
Sign up to set email alerts
|

Loss of EZH2 results in precocious mammary gland development and activation of STAT5-dependent genes

Abstract: Establishment and differentiation of mammary alveoli during pregnancy are controlled by prolactin through the transcription factors STAT5A and STAT5B (STAT5), which also regulate temporal activation of mammary signature genes. This study addressed the question whether the methyltransferase and transcriptional co-activator EZH2 controls the differentiation clock of mammary epithelium. Ablation of Ezh2 from mammary stem cells resulted in precocious differentiation of alveolar epithelium during pregnancy and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 69 publications
(107 reference statements)
1
39
0
Order By: Relevance
“…Deletion of Ezh2 did not adversely affect the genome-wide H3K27me3 landscape of alveolar cells but led to their accelerated differentiation during pregnancy (32). Mechanistically, EZH2 binds to target genes and thus controls the genomic access of EZH1, RNA polymerase II (Pol II), and STAT5 (32). Since genes key to mammary development and differentiation are bound by EZH2 but not decorated by H3K27me3 marks (32), we propose the possibility that active demethylation of these loci is an essential step in these programs.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…Deletion of Ezh2 did not adversely affect the genome-wide H3K27me3 landscape of alveolar cells but led to their accelerated differentiation during pregnancy (32). Mechanistically, EZH2 binds to target genes and thus controls the genomic access of EZH1, RNA polymerase II (Pol II), and STAT5 (32). Since genes key to mammary development and differentiation are bound by EZH2 but not decorated by H3K27me3 marks (32), we propose the possibility that active demethylation of these loci is an essential step in these programs.…”
mentioning
confidence: 89%
“…Frozen stored mammary tissues from female virgin and p13 mice were broken into powder with a mortar and pestle. Samples were processed as previously described (32). The following antibodies were used for immunoprecipitation: anti-KDM6A (Sigma; HPA002111) and anti-H3K4me1 (Abcam; ab-8895).…”
Section: Mec Isolation and Facs Analysis Mammary Epithelial Cells (Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarded as PRC2’s canonical methyltransferase, EZH2 plays a major role in catalyzing di- or tri-methylation of H3K27 in many cell types. Loss of Ezh2 results in embryonic lethality (O’Carroll et al, 2001), aberrant cell differentiation (Ezhkova et al, 2009; Snitow et al, 2016; Snitow et al, 2015; Su et al, 2003; Yoo et al, 2015) and cell proliferation arrest (Bracken et al, 2003). In contrast, Ezh1 depletion does not reduce global H3K27me2/3 levels (Margueron et al, 2008), or impact viability and fertility in mice (Ezhkova et al, 2011; Margueron et al, 2008), suggesting EZH2 alone is sufficient to fulfill the biological functions of PRC2 for most tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The loss of EZH2 from mammary stem cells resulted in enhanced differentiation of alveolar epithelium and the activation of mammary-specific STAT5 target genes during pregnancy [67]. In addition, these studies showed that EZH1 and EZH2 can serve redundant functions in the formation of mammary alveoli, but the presence of EZH2 was necessary to control progressive differentiation of milk secreting epithelium during pregnancy [67]. Overall, studies in the three different tissue types show that the methyltransferase and transcriptional coactivator EZH2 can modulate the several activities of STAT5.…”
Section: Stat5 Interacting Proteinsmentioning
confidence: 99%